EEG Patterns Orienting to Lafora Disease Diagnosis—A Case Report in Two Beagles - Demeny, Helga; Florea, Bogdan; Tabaran, Flaviu; Danciu, Cecilia Gabriella; Ognean, Laurent (Frontiers in Veterinary Science, 2020)
Lafora Disease (LD) is a rare, fatal, late-onset, progressive form of myoclonic epilepsy, occuring in humans and dogs. Clinical manifestations of LD usually include seizures, spontaneous and reflex myoclonus with contractions of the neck and limb muscles. We studied the electroencephalogram (EEG) patterns of two beagles in whom LD was subsequently confirmed by genetic testing. In both cases, the EEG recordings, accompanied by electromyography (EMG), have shown similar uncommon patterns. The hypovoltaged background rhytm was interrupted by waxing “crescendo” polyspikes-slow wave complexes appearing 80‒250 ms after the start of intermitent photic stimulation, followed by myoclonic jerks after 80‒150 ms. This study highlights the value of EEG in establishing a presumptive diagnosis of LD in dogs.